Clinical Characteristics of Tuberculosis Among People Living with Human Immunodeficiency Virus (HIV) A Multicenter Study - Balik, Recep; Karacaer, Zehra; Akca, Veysel; Kaya, Buelent; Akbulut, Ilkay; Oz, Esra Duru; Kurtaran, Behice (Erciyes Univ Sch Medicine, 2024)
3Department of Infection Diseases and Clinical Microbiology, Mu & gbreve;la Training and Research 6Department of Infection Diseases and Clinical Microbiology, Etlik City Hospital, Ankara, T & uuml;rkiye 8Department of Infection Diseases and Clinical Microbiology, Antalya Training and Research 9Department of Infection Diseases and Clinical Microbiology, 4ukurova University Faculty of 11Department of Infection Diseases and Clinical Microbiology, University Health Sciences
Keywords: Diseases and Clinical; & Idot;stanbul; T & uuml;rkiye; Antiretroviral therapy; co-infection; human immunodeficiency virus (HIV)